Association of parental methylenetetrahydrofolate reductase (MTHFR) C677T gene polymorphism in couples with unexplained recurrent pregnancy loss - Anil Kumar Sah; Nisha Shrestha; Pratikshya Joshi; Renu Lakha; Sweta Shrestha; Laxmi Sharma; Avinash Chandra; Neetu Singh; Yuvraj KC; Bhola Rijal (BMC Research Notes, 2018)
Abstract Objective The aim of this study was to identify the association of parental MTHFR C677T gene polymorphism in couples with and without RPL history. Results During the study, 21.4% (15/70) of Ala222Val polymorphism was observed among RPL couples while no polymorphism was seen among normal, healthy couples. Our study did not find any association between MTHFR C677T polymorphism and gender (p > 0.05), gestational period (p > 0.05), geographical region (p > 0.05) and menstrual history (p > 0.05). However, significant association was seen between MTHFR C677T polymorphism and number of losses (p < 0.05), concluding that the risk of the polymorphism increased with the increase in number of losses. Significant variation in the MTHFR C677T genotype with number of losses among RPL couples were seen but not with other study variables.